A case report: A rare case of icteric variant of Stauffer's syndrome - Abiharan, P.; Balagobi, B.; Gobishangar, S.; Senthuran, R.; Thulasi, T. (Elsevier, 2023)
Introduction: Stauffer's syndrome is a rare paraneoplastic non metastatic hepatic dysfunction related to renal cell carcinoma. It is characterized by elevated alkaline phosphatase, erythrocyte sedimentation rate, a-2-globulin, y- glutamyl transferase, thrombocytosis, prolongation of prothrombin time and hepatosplenomegaly, in the absence of hepatic metastasis. A rare variant of it with cholestatic jaundice is described in four cases so far in literature. Clinical presentation: We present a case of a patient presented with features of cholestatic jaundice who was found to have a left sided renal cell carcinoma in the work up. Discussion: This case illustrates the importance of considering paraneoplastic syndromes in mind when working up for patients presenting with hepatic dysfunctions without identifiable causes. Conclusion: This may result in early identification and intervention which will result in better outcome and prolong survival rate.
Keywords: Stauffer's syndrome; Paraneoplastic syndrome; Renal carcinoma; Cholestatic jaundice; Bosnaik cysts